TINJAUAN HUKUM ISLAM TERHADAP FAKTOR PENYEBAB TINGGINYA ANGKA CERAI GUGAT (Studi Kasus di Pengadilan Agama Ponorogo Tahun 2017-2019) - Wahyudi (IJoIS: Indonesian Journal of Islamic Studies, 2020)
Abstract. Divorce is the last alternative way (emergency door) that can be passed by husband and wife if the relationship (household) cannot be maintained in its integrity and continuity. Divorce is here the initial problem that arises is triggered by economic factors that cause new problems. The method used in this study is a qualitative research method that produces descriptive data analysis. The data from this study is primarily in the form of annual reports from the Ponorogo Religious Court, while the secondary sources are library materials in the form of books and interviews with judges. The data collection techniques are documentation and interviews. The results of this study are 1) Economic factors as the cause of the high rate of divorce in the Ponorogo Religious Court of 76.57%. The judge filed a lawsuit with the consideration that the consideration of light mafsadah that must be taken from the heavy madharat among that mafsadah, 2) The factors that hinder continuously reached 12.48%, In this case, the judge decided based on the Compilation of Islamic Law article 116 item f. 3) The factor of leaving one of the parties is 9.79%. In this case, the judge is based on KHI Article 116 letter b.